If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -36 = 6x + 20 Reorder the terms: -36 + -2x = 6x + 20 Reorder the terms: -36 + -2x = 20 + 6x Solving -36 + -2x = 20 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -36 + -2x + -6x = 20 + 6x + -6x Combine like terms: -2x + -6x = -8x -36 + -8x = 20 + 6x + -6x Combine like terms: 6x + -6x = 0 -36 + -8x = 20 + 0 -36 + -8x = 20 Add '36' to each side of the equation. -36 + 36 + -8x = 20 + 36 Combine like terms: -36 + 36 = 0 0 + -8x = 20 + 36 -8x = 20 + 36 Combine like terms: 20 + 36 = 56 -8x = 56 Divide each side by '-8'. x = -7 Simplifying x = -7
| 5x^2*y^2-20xy= | | x^2-36=3x | | -1+5+-15+1+-2+5+1+-6= | | X+3x-6=90 | | 6x+2y=23.52 | | -8+15+-2+-15+-4+13+-17+11= | | 6k-3-2k=k-22 | | x*x-14x+33=0 | | -5=-2-3 | | -6z=3x | | x=-7+7 | | 7-8x=87-43x | | 2x-8y=-11 | | 30x*-6= | | 20x-45= | | -7x+5=48+x+45 | | y=-2(-7+y)+7 | | 2x-y+2z=-8 | | 2x^2+x-3=18 | | 4(7x-1)=5(2x+1) | | (2x-17)+1x+59=360 | | 4x+20=45-x | | x=18+-7(2) | | 2x-2=-8+3x | | 5(y-3)-3(y-2)=8 | | (3)/(8)x-(1)/(4)=2 | | 40-x=12x | | 48=4n/7+n | | -8(-3)(-3)= | | y=-4(18+-7y)+18 | | 4z-11-z+2=0 | | -2x(5x-8)=6x |